We Live the Innovation of Mobile Devices’ Inclusion in the Education - Pulido Huertas, Diana Carolina; Nájar Sánchez, Olga; Guesguan Salcedo, Lady Giovanna (Universidad Pedagógica y Tecnológica de Colombia, 2016)
This study will present the characterization related to the use of digital competences of some primary teachers from a public institution in Tunja, by using activities with tablets in order to consolidate a digital culture. The incorporation of digital individual devices for students and teachers of different education levels will be transformed into a main tendency in the current governmental politics of digital inclusion, social inclusion and educational opportunities’ improvement of Iberoamerican educational systems.